Osculatings hyperquadrics - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2007)
In this article the linear systems of osculating hyperquadrics are considered which are intrinsically defined by the distribution of flags on grassmannians Gr(m, n) of the affine space An.
Keywords: Grassmann manifold; flag; osculating hyperquadric